Physical, chemical and microbiological characterization of the intertidal sediments of Pereque Beach, Guaruja (SP), Brazil - de Oliveira, Ana Julia Fernandes C.; Hollnagel, Heloisa C.; Lima Mesquita, Hilda de S.; Fontes, Roberto Floravanti C. (Elsevier B.V., 2007)
Physical and chemical characteristics of intertidal sediments and their relationships with bacteria and cyanobacteria, were analyzed at four stations at Pereque Beach. Granulometric analysis showed that Pereque beach has sediment that is classified as sand. The lowest value of the sediment C/N rates (6.08), mainly due to a higher concentration of organic nitrogen, was found at the northern part of Pereque Beach, where organic matter of marine source was more prominent. In this area, density (9.6 x 106 cells cm(-3)), biomass (1992.04 ngC cm(-3)) and activity of bacteria were higher than at the southern end. In contrast, cyanobacteria density varied from 2.0 to 4.0 x 10(5) cells cm(-3), with biomass and total chlorophyll a of the sediment being higher at the southern part, where there are water input from Pereque River and higher organic matter of continental origin. The variability in the microbial population is discussed in the light of the sediment granulometry, organic matter quality, fresh water inflow and pollution. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: bacteria; cyanobacteria; sediments; microbial activity